A study of linguistic features of Adjectival phrases denoting personality in english and their vietnamese equivalents (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis has been done in an effort to investigate the linguistic features of adjectival phrases denoting personality in English and their Vietnamese equivalents. The data for analysis guaranteeing the validity and reliability of the samples are mainly taken from bilingual novels, stories and websites. Through the adoption of a qualitative approach, the researcher analyses and describes various samples to find out the syntactic, semantic, and pragmatic features of adjectival phrases denoting personality in English and their Vietnamese equivalents. With the description, analysis and comparison between the devices in English and those in Vietnamese, the findings will serve as a foundation to put forward a number of implications for English language teaching, learning and especially in translating.